The extractive business model of private equity firms in the German healthcare sector and the crisis in social reproduction - Brigitte Young (Review of Evolutionary Political Economy, 2025)
The paper explores the contradiction between the extractive business model of the private equity buy-outs of the German healthcare sector and the crisis of reproduction, which has the potential not only to undermine the solidaristic healthcare system, but also to undermine the idea of societal protection as the object of socio-economic governance. Drawing on the insights of the international/comparative political economy and feminist literature opens an analytical space to connect the macro-financialized economy to the non-economic sphere of social reproduction and, in the process, uncover the contradictory nature of this relationship. From the vantage point of the financial crisis of 2007, the private equity industry was the beneficiary of the consecutive switch of major central banks to unconventional monetary policy and exceptionally low interest rates swamping the market with liquidity. Private equity managers and their shareholders are the big winners due to their extraordinary financial power, but this has dire consequences for the (mostly female) staff, the patients, and the wider solidaristic healthcare community. Moreover, since private equity firms operate through complex and opaque international holding structures, these entities have little to fear from German national regulatory powers to ban or prohibit tools of financial engineering such as debt push-down, asset stripping, and tax evasion; this creates a high level of uncertainty as to the impact of PEs on the sustainability of the German social market economy as a whole.
Keywords: B54; B59; D60; E00; E52; G23; I11; 320; Private equity industry; Political economy; Feminist economics; Unconventional monetary policy; German healthcare system; Social reproduction